2015
DOI: 10.1177/1758573214567558
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided platelet-rich plasma injection for distal biceps tendinopathy

Abstract: Background: Distal biceps tendinopathy is an uncommon cause of elbow pain. The optimum treatment for cases refractory to conservative treatment is unclear. Platelet-rich plasma has been used successfully for other tendinopathies around the elbow. Methods: Six patients with clinical and radiological evidence of distal biceps tendinopathy underwent ultrasound-guided platelet-rich plasma (PRP) injection. Clinical examination findings, visual analogue score (VAS) for pain and Mayo Elbow Performance scores were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 24 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…Growth factors regulate and stimulate cellular processes during healing. Furthermore, the fibrin clot of PRP provides a matrix for the migration of cells responsible for healing (14,25). Our results are also consistent with findings obtained in previous studies reported that the using of PRP alone or combined with other types of the graft can shorten the required time for tendon healing (6,14).…”
Section: Discussionsupporting
confidence: 91%
“…Growth factors regulate and stimulate cellular processes during healing. Furthermore, the fibrin clot of PRP provides a matrix for the migration of cells responsible for healing (14,25). Our results are also consistent with findings obtained in previous studies reported that the using of PRP alone or combined with other types of the graft can shorten the required time for tendon healing (6,14).…”
Section: Discussionsupporting
confidence: 91%
“…Although recent investigations have demonstrated clinical success with use of US-guided injections for distal bicep tendinopathy [5,6], this article is the first to describe a posterior approach to this area on a live subject, which we believe to be very important for the safe, easy, and effective delivery of the injectate. We believe that a significant risk of injury exists with an anterior approach because of the multiple neurovascular structures in the area and increased difficulty in visualizing the tendon.…”
Section: Discussionmentioning
confidence: 97%
“…However, one set of investigators [4] noted a 27% percent complication rate, with the most common complications being nerve dysfunction and radioulnar synostosis. Use of platelet-rich plasma (PRP) has been reported as a potential alternative treatment for this condition [5,6]; however, an anterior approach has been used to inject the PRP, which increases the chance of a neurovascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable controversy exists about the long head of the biceps (LHB) tendon roles and functions, but the majority of scientists agree that the function of LHB is in humeral head depression and its anterior stability (1,2). Inflammatory tendinopathy in LHB tendon is one of the most common causes of shoulder pain that mainly induces weakness in forward flexion of the shoulder (2).…”
Section: Introductionmentioning
confidence: 99%